Effect of practice on similar and dissimilar skills in patient transfer through training with a robot patient. (19th March 2019) - Lin, Chingszu; Huang, Zhifeng; Kanai-Pak, Masako; Maeda, Jukai; Kitajima, Yasuko; Nakamura, Mitsuhiro; Kuwahara, Noriaki; Ogata, Taiki; Ota, Jun
ABSTRACT: With the number of hospital stays increasing, nurses require more training to handle a variety of patients. However, time for training in nursing schools is limited, and students lack the opportunity to practice on a diverse variety of patients. Using a robot to simulate actual patients, this study observes the learning transfer effect of practice on practice-similar and practice-dissimilar skills from one patient to another, and investigates which types of practice suit which kinds of training. An experiment was conducted by administering a pre-test, practice, a post-test, and a transfer test to two groups ( N  = 8), each with different practice-related skills. The evaluation used a checklist covering required skills that were either similar or dissimilar across groups, depending on their practice. The effect of practice can be observed through a comparison of skills similar to one group but dissimilar to the other. The results show that practice facilitates learning transfer on similar skills but not, or to a lesser degree, on dissimilar skills. Furthermore, if skills needed to handle given symptoms are unfamiliar or inaccessible to students, practice related to those symptoms should be emphasized through simulated training with robots. GRAPHICAL ABSTRACT: